Islamic Scriptures and Voice Intonation: A Preliminary Survey in Arabic Linguistic Thought and ?ad?th Interpretive Discourse (KEMANUSIAAN The Asian Journal of Humanities, 2019)
This is the first study that aims to explore the possibility of applying the art and science of voice intonation in reading statements attributed to the Prophet Muhammad and to form a theoretical framework explicative of the nexuses between the two enterprises. The study ventures to assess the attention towards a range of functions played by voice intonation such as attitudinal functions, psychological functions and other indicative functions as it may have appeared within the various compositional strategies of ?ad?th literature. It also aims to examine how normal conversations, declarative sentences, questions, etc. could be identified through voice intonation and the extent to which the understanding of a certain ?ad?th can be affected by such an exercise. The preliminary analysis indicates that the right selection of tone assumes a crucial role in forming a sound ?ad?th interpretation. The consequential extension of this study may involve several other subtopics in the field such as the oral and written transmission of ?ad?th, the euphony and cacophony of narrated words and sentences in ?ad?th, and the psycho-spiritual effects of ?ad?th.